MELACAK AKAR RADIKALISME DALAM GERAKAN ISLAM MODERN - Mizan, Aguk Irawan (Universitas Islam Negeri Raden Intan Lampung, 2011)
Radicalism has a deep root in Islamic teachings. Amounts of verses and traditions in the view of literal-formalistic reading are inspiring to shape the selected teachings and the ownership of absolute truth. Both of these principles spring exclusive and superior attitude in the face against the other, also they position of each dissident man as an enemy who must be conquered by any way, even violent way. This writing tries to analyze theological root of radicalism growing in the thought of Islamic sphere, as well as movements/organizations that are representing the radical theology such as Jama’ah al-Ikhwa>n al-Muslimu>n.